Advocacy for the Efficacy and Reinstatement of Funding Federal Even Start Family Literacy Grant Programs - Judith J. Smith (Arizona State University, 2011)
The Even Start Family Literacy model builds coalitions of community partners that build learning communities throughout our nation. The problem for stakeholders in family literacy programs is how to continue funding to encourage success and sustainability of programs.  The focus of the study was twofold: 1) the importance of using data from national studies to make program improvements 2) the importance of making program improvement prior to reducing or rescinding funding for the Even Start Family Literacy Program. This quantitative study identified program, participant, and funding characteristics that state and local educators can target for program improvement. Programs must demonstrate measurable outcomes of success for adults and children.